Diffusion of Drip Irrigation: The Case of California. (19th January 2017) - Taylor, Rebecca; Zilberman, David
Abstract: This article provides insights regarding the state of the literature on the economics of drip irrigation adoption and diffusion. Our literature review finds that the methodological approaches to studying diffusion—conceptual modeling, empirical analysis, and historical narratives—are complementary, yet historical analyses have been underemphasized. To address this gap, we conduct a historical analysis of the diffusion of drip irrigation in California. Our forty‐five‐year narrative highlights that the successful adoption of drip irrigation to diverse crops and locations required (i) coevolution of the technology and complementary production processes, and (ii) joint efforts by private and public experts at the local level.